Intersectional socialism : a utopia for radical interdependence - Masquelier, Charles (Bristol University Press, 2023)
In the context of sustained economic and environmental crises, marked by extreme inequalities of wealth, rising xenophobia, racism and precarity, never has the need for a radical change of system been so pressing. This book is an invitation to think the world otherwise. The author breathes new life into socialist thought through the deployment of an intersectional lens, bringing diverse struggles for emancipation both within and outside the Global North into dialogue with one another. In doing so, he offers the kind of bold and holistic thinking the present situation calls for.